Donnes qualitatives et quantitatives sur le microphytobenthos des fonds sablonneux et vaseux du litoral roumain du la Mer Noire - Bodeanu, Nicolae (Cercetări Marine - Recherches Marines, 2026)
The systematic composition of the mobile micro- benthic sediments are analyzed as well as the participation of plankton to building the former, the composition of benthic micro fila per ecological groups and the most frequent and quantitatively main species. Data are given regarding the quantitative distribution of microphytobenthos depending on the underlying layers and depth, at various times, the annual density dynamics and average monthly biomass, the average yearly values and overall stock of benthic microflora in the area investigated. The paper also describes the equipment of original construction used for collecting quantitative samples.